SOSIALISASI PENGGUNAAN APD PADA SAAT PRAKTEK KLINIK KEPADA SISWA SMK KESEHATAN TNI AL MAKASSAR - Rosmaladewi Talli; Ariyani Goeliling (Gapenas Publisher, 2021)
The need for health services is increasing in line with population growth and increasing public knowledge and awareness about the importance of health. This increase in need concerns the increase in the number and size of a health facility, including a dental clinic, which impacts increasing the number of workers, where these workers have a high chance of potentially hazardous health hazards. According to the World Organizational organization, one of the efforts to provide labour protection for Occupational Safety and Health in the dental clinic is providing personal protective equipment. With the socialization of the use of (PPE), it is hoped that the Makassar Navy Health Vocational School students will protect themselves in their clinical practice. And evaluation. The result of the implementation of this socialization is an increase in the knowledge of the Makassar Navy Health School students regarding PPE used during clinical practice